Taman Keanekaragaman Hayati Hutan Pelawan Sebagai Media Pendidikan Keanekaragaman Hayati Lokal di Provinsi Kepulauan Bangka Belitung - Akbarini, Dian; Iskandar, Johan; Purwanto, Bambang Heru; Husodo, Teguh (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Biodiversity Park in Central Bangka Pelawan Forest is one of the park that uses the concept of in-situ conservation in its conservation category. The development of this park was initiated by the Regional Government of Central Bangka Regency which aims to protect local biological resources, specifically the Pelawan Merahtree (Tristaniopsis merguensis). This area was designated as a park with three priority functions: ecotourism, education and research. The purpose of this study is to find out whether the educational function has been carried out properly in accordance with the initial purpose of the construction of this park. The method used is a mixed method with data collection techniques through interviews and questionnaires, the selection of respondents was carried out by purposive sampling. The results of the study showed that only 18.18% visited the park as a place of learning, the most objective of visitors was for recreation (56.82% ), visitors who are aware of the use of the park in (53, 64%) . The visitors (62,37 %) also think that facilities must be added, including information boards, leaflets or brochures to convey knowledge of biodiversity and visitors (92,27%) said the importance of the attendance of officials as informants to convey knowledge and information related to biodiversity in the park